Living With Huge Rectal Prolapse and Rectocele: A Sad Story of a Rural Nepalese Woman - Rana, Apariharya; Rana, Ashma (Nepal Journal of Medical Sciences, 2021)
A postmenopausal multiparous woman with defecation difficulty for over three and half years upon clinical examination was diagnosed as a case of huge rectal prolapse with rectocele during a health camp organized by Perinatal Society of Nepal in Sindhupalchok. She was referred to a tertiary care center so that she could undergo combined corrective surgery in the same sitting: rectal prolapse by Surgeons and rectocele by Gynecologists. Unfortunately, she was returned home with a scheduled elective operative appointment a few months later, which she failed to make owing to the long distance from home to hospital. Her case could not be followed, as the contact number she left was unreachable. This case represents an example for many women who have to live with suffering, their problems overlooked by both families and institutions, a situation in dire need of a solution.